Physics of Wurtzite Nitrides and Oxides Passport to Devices - Gil, Bernard; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book gives a survey of the current state of the art of a special class of nitrides semiconductors, Wurtzite Nitride and Oxide Semiconductors. It includes properties, growth and applications. Research in the area of nitrides semiconductors is still booming although some basic materials sciences issues were solved already about 20 years ago. With the advent of modern technologies and the successful growth of nitride substrates, these materials currently experience a second birth. Advanced new applications like light-emitters, including UV operating LEDs, normally on and normally off high frequency operating transistors are expected. With progress in clean room technology, advanced photonic and quantum optic applications are envisioned in a close future. This area of research is fascinating for researchers and students in materials science, electrical engineering, chemistry, electronics, physics and biophysics. This book aims to be the ad-hoc instrument to this active field of research.
Crystallography and Basic Physical Properties -- Band Structure and Semi-Classical Theory of the Dielectric Constant -- Growth and Structural Characterization( X-Ray, AFM, TEM) of Bulk Materials and Thin Films, Heterostructures -- Optical Properties of Wurtzite Epilayers -- Optical Properties of Low-Dimensional Nitride Heterostructures -- Photonic Devices -- Transport Properties in Nitrides -- Transistors -- Quantum Devices.
Keywords: Semiconductors; Optical materials; Electronic materials; Electrical engineering; Electronic circuits; Semiconductors; Optical and Electronic Materials; Electrical Engineering; Electronic Circuits and Devices